The Role of Local Government, Religious and Community Figures, In Conjunction With the Security Forces (Polri) In Returning A Harmonic Life Post Conflict As Ethnic In Sambas Regency - Setyo Utomo (STKIP Singkawang, 2018)
Humans as God's creatures are given freedom of human rights from birth. As a citizen, it is necessary that the State shall be obliged to protect the freedom of the rights of its citizens. However can’t be denied the freedom of human rights between human beings with each other in fact lead to differences in interests that led to the emergence of conflicts that often lead to the occurrence of fatalities and loss of property. Whereas one of the citizens' rights is free to live anywhere within a territory of the State. Likewise with citizens of Indonesia, in the Constitution of the State has guaranteed the freedom to reside within the territory of the Unitary State of the Republic of Indonesia. Based on the experience of conflicts in the country, with the post-conflict handling of those who had previously conflicted it can be reunited in living a harmonious life, but unlike the conflict that occurred in Sambas Regency in 1999 between ethnic Malays and Madurese which has been over the years and with post-conflict efforts that have been done until now people in Sambas district have not been able to accept the presence of Madurese in Sambas Regency.